Effects of strength vs. endurance training and their combination on physical performance characteristics in female horseback riders - Hyttinen, A. M.; Häkkinen, K. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The purpose of this study was to investigate effects of strength (S), endurance (E) and concurrent strength and endurance (SE) training on neuromuscular and cardiorespiratory characteristics during the 12-week volume-equated protocols in female horseback riders. METHODS: Subjects (N.=44) (29.4±8.9 yrs) were assigned to S (N.=11), E (N.=11), SE (N.=13) and control (C) (N.=9) groups. Training consisted of progressive S, E or SE training 3x/week and riding exercise 4-6x/week. The measurements included maximal isometric bilateral leg press force (MVCLP) and EMG of VL and BF muscles, rapid isometric force production (0-500ms), maximal force of trunk extensor/flexors (MVCE/MVCF), countermovement-jump (CMJ), maximal oxygen uptake (VO2max), cycling-time (Timemax), blood lactate (L) and heart rate (HR) in the bicycle-ergometer test. RESULTS: Only group S showed significant increases of 9% in MVCLP (P<0.01) and 3% in MVCE (P<0.05) forces. None of the groups showed significant increases in CMJ, rapid isometric force production or EMG. Timemax in the ergometer test increased significantly in S (P<0.05), SE (P<0.05) and E (P<0.01) with significant increases in VO2max in E (P<0.05) and SE (P<0.01). CONCLUSIONS: The present strength-training program led to the significant gain in maximal strength in S but not in SE, maybe due to some interference effects produced by the actual endurance training and riding related endurance training. All groups increased significantly Timemax but VO2max increased only in E and SE. It would be useful for female horseback riders to perform combined SE training and to perform S training periodically to insure gains in strength, when needed.